A guide to emerging technologies for large-scale and whole brain optical imaging of neuronal activity - Weisenburger, Siegfried (Annu Rev Neurosci, 2018)
The mammalian brain is a densely interconnected network that consists of millions to billions of neurons. Decoding how information is represented and processed by this neural circuitry requires the ability to capture and manipulate the dynamics of large populations at high speed and resolution over a large area of the brain. While there has been a rapid increase in use of optical approaches in the neuroscience community over the last two decades, most microscopy approaches lack the ability to record the activity of all neurons comprising a functional network across the mammalian brain at relevant temporal and spatial resolution. In this review, we survey the recent development in the optical calcium imaging technologies in this regard and provide an overview of the strengths and limitations of each modality and their potential for scalability. We provide a guidance from a biological user perspective that is driven by the typical biological applications and sample conditions. We also discuss the potential for future advances and synergies that could be obtained through hybrid approaches or other modalities.